Pengembangan dan Evaluasi Kurikulum Pendidikan Di Pondok Pesantren Desa Ganjaran Gondanglegi Malang - Yazidul Busthomi (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2020)
Islamic boarding schools in Ganjaran village are Islamic educational institutions. However, curriculum development and evaluation in this boarding school, there is still no data that can be ascertained, so it is interesting to study. Then the researcher raised the title